An Organ of Murder: Crime, Violence, and Phrenology in Nineteenth-Century America - Thompson, Courtney E. (Critical Issues in Health and Medicine, 2021)
Frontmatter -- Contents -- Illustrations -- Introduction: Through a Mirror, Darkly -- Chapter 1 Origins and Organs -- Chapter 2 Transatlantic Societies and Skulls -- Chapter 3 Phrenology on Trial -- Chapter 4 The Prison as Laboratory -- Chapter 5 Policing the Self and the Stranger -- Chapter 6 A Victory for Phrenology? -- Epilogue: Phrenological Futures -- Acknowledgments -- Notes -- Bibliography -- Index -- About the Author